Corrigendum to “Assessing sexual health literacy among Thai female adolescents in non-formal education: A mixed-methods study” [Belitung Nursing Journal, 2025; 11(3): 340-348] - Rapeepan Narkbupha; Atcharawadee Sriyasak; Atiya Sarakshetrin; Pailin Thungthin (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
This corrigendum corrects clerical errors regarding the study timeline, IRB approval dates, the instrument permission date, and adolescent age classifications in the original article (DOI: https://doi.org/10.33546/bnj.3744), which resulted from an inadvertent mistake in converting Buddhist Era (BE) dates to the Gregorian calendar. The authors confirm that these administrative corrections do not affect the methodology, data analysis, results, or conclusions of the original study and sincerely apologize for any inconvenience caused.